Uptake of Cystine by the Yeast Phase of Histoplasma capsulatum - Gilbert, Brian E. (1970)
This report deals with factors affecting the uptake of cystine by the yeast phase of Histoplasma capsulatum. The kinetics of uptake showed a saturation at 70 μM and an average K(m) value of 3 × 10(−5)m. The optimal pH and temperature for transport of cystine were 6.5 and 37 C, respectively. The energy of activation was 14.1 kcal/mole, and the temperature coefficient value was 2.1. A requirement for energy supplied by metabolic activity was demonstrated by the inhibition of incorporation of the amino acid by cells preincubated with either 2,4-dinitrophenol or sodium azide. Although uptake was not inhibited by any single amino acid, a combination of amino acids did cause a decrease in uptake. Thus, the data show that the uptake of cystine by yeast cells of H. capsulatum has the characteristics of a system of transport that requires the expenditure of energy by the cells.